2022
DOI: 10.26509/frbc-wp-202220
|View full text |Cite
|
Sign up to set email alerts
|

Greater Than the Sum of the Parts: Aggregate vs. Aggregated Inflation Expectations

Abstract: Using novel survey evidence on consumer inflation expectations disaggregated by personal consumption expenditure (PCE) categories, we document the paradox that consumers' aggregate inflation expectations usually exceed any individual category expectation. We explore procedures for aggregating category inflation expectations, and find that the inconsistency between aggregate and aggregated inflation expectations rises with subjective uncertainty and is systematically related to socioeconomic characteristics. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This is an example of media-based risk-amplification. Dietrich et al (2022) reported results of a survey carried out between July 2020 and September 2021. They found that direct estimates of expected inflation were higher than indirect estimates obtained by aggregating expectations across product categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an example of media-based risk-amplification. Dietrich et al (2022) reported results of a survey carried out between July 2020 and September 2021. They found that direct estimates of expected inflation were higher than indirect estimates obtained by aggregating expectations across product categories.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, "the heuristics involved in expressing aggregate expectations may differ from the processes underlying aggregated inflation expectations" (p25). Thus, Dietrich et al (2022) argue that both direct and indirect (aggregated) inflation expectations are derived from respondents' personal experience with prices but via different cognitive processes. But, in their study, direct estimates of inflation were higher than inflation expectations in any one product category.…”
Section: Discussionmentioning
confidence: 99%
“…Our sample was collected as part of a daily online survey of consumer expectations conducted by the Federal Reserve Bank of Cleveland and administered by Qualtrics Research Services (see Knotek et al (2020); Dietrich et al (2022); Coibion et al (2023b)). Respondents are representatively drawn from several actively managed, double-opt-in market research panels, complemented using social media (Qualtrics 2019).…”
Section: Survey Backgroundmentioning
confidence: 99%
“…11 See https://www.bundesbank.de/en/bundesbank/research/survey-on-consumer-expectations. 12 A recent study in this regard is presented by Dietrich, Knotek et al (2022) who evaluate consumers' expectations of price growth in subcategories of goods included in the consumer price index versus their expectations of aggregate inflation. The authors find that consumers' expectations of price changes in individual goods categories are lower, less volatile, and exhibit lower disagreement than their expectations of aggregate individual.…”
Section: E N D N O T E Smentioning
confidence: 99%